2018
DOI: 10.3390/met8020113
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behavior of AA1050H24-Graphene Nanocomposite Obtained by Friction Stir Processing

Abstract: The tribological behavior of a new composite material containing graphene nanosheets (GNS) is presented. The composite material was obtained by Friction Stir Processing, using as metallic matrix the AA1050-H24 alloy. Different tool rotation and advancing speeds were tested in friction stir processing (FSP). The worn surfaces of obtained materials were analyzed by Scanning Electron Microscopy (SEM). Raman spectroscopy demonstrated that graphene reinforcements are successfully mixed into the aluminum matrix. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Jeon et al 12 reported a 15% increment in the thermal conductivity of aluminum alloys when reinforced with graphene and fabricated via FSP. Blanco Fernandez et al 13 also noticed a reduction in wear loss with AA1050H24graphene composite fabricated by FSP. Khodabakhshi et al 14 reported $53% increases in hardness and more than three times increase in the yield strength (YS) of the Al-Mg/graphene nanocomposite fabricated by FSP.…”
Section: Introductionmentioning
confidence: 88%
“…Jeon et al 12 reported a 15% increment in the thermal conductivity of aluminum alloys when reinforced with graphene and fabricated via FSP. Blanco Fernandez et al 13 also noticed a reduction in wear loss with AA1050H24graphene composite fabricated by FSP. Khodabakhshi et al 14 reported $53% increases in hardness and more than three times increase in the yield strength (YS) of the Al-Mg/graphene nanocomposite fabricated by FSP.…”
Section: Introductionmentioning
confidence: 88%
“…This causes the wear resistance to be more limited compared to the other types of reinforcements. 77,78…”
Section: Resultsmentioning
confidence: 99%
“…This causes the wear resistance to be more limited compared to the other types of reinforcements. 77,78 When N4 and N5 composites were examined in Figures 13(c) and (d), the orientation of the grains caused by the ECAP effect with severe plastic deformation was observed. The obtained images are also supported by various studies.…”
Section: Resultsmentioning
confidence: 99%
“…The large surface of the graphene sheets favours its strong interfacial connection with the metal phase of the composite. In solid state preparation of Al-graphene composite by FSW, a huge decrease in the degree of wear is also observed [21]. In another study conducted by Jeon et al [22] the thermal conductivity of a graphene-reinforced composite is increased by near 15% when obtained by FSW.…”
Section: Overlapping Fsw Of Aluminum Alloy Aa6061 With Intermediate Graphene Layermentioning
confidence: 94%